Primitive hemocholecyst with hemobilia due to hemorrhagic cholecystitis - Baldizán, Jorge W.; Estefan, Alberto; Abascal, Winston; Falconi, Luis M. (Cirugía del Uruguay, 1978)
The authors refer to a case of primitive hemocholecyst with hemobile due to hemorrhagic cholecystitis. The case is discussed- with reference to diagnosis and treatment of this rare complication of cholelithiasis.